Physiotherapy service needs: physicians' perception and patient referral in HUKM - Ayiesah Ramli (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2003)
The purpose of this study is to identify the Physicians' perception of the professional image of the physiotherapists in HUKM, the reasons for patient referral to the physiotherapists and whether the perception have influence on patient referral. A two-part questionnaire was used to survey the sample of doctors. The first part contained demographic variables whereas the second part contained attitudinal statements based on Moore's criteria of professionalism and reasons for referral. Two hundred questionnaires were distributed and one hundred and sixteen were returned. The results indicated that the responding doctors viewed the physiotherapists as possessing some degree of professionalism, However there was relatively less agreement with the professional aspect of knowledge, skills and autonomy of judgement posed by the physiotherapist. Spearman correllation demonstrates positive association (p<0.05) between the Physicians' perception and the referral of patient to the pliysiotherapists.